Testing of measurement instrument software on the national level - Velychko, Oleh; Gordiyenko, Tetyana; Hrabovskyi, Oleh (Eastern-European Journal of Enterprise Technologies, 2018)
Features of software for measuring instruments are considered. A comparative analysis of the general requirements in the documents and guidelines of the international and regional organizations of legislative metrology OIML and WELMEC concerning the testing of software for measuring instruments was carried out. The main factors that are monitored during quality testing of software for measuring instruments were identified by constructing Ishikawa cause-effect diagrams based on the requirements of the OIML document and the WELMEC guide. The possibility of joint use of the requirements of the OIML document and the WELMEC guide for testing the MI SW was analyzed. The general Ishikawa cause-effect diagram was developed, its main factors can be used for the development of special checklists for testing the MI SW taking into account different risk classes. The algorithms for testing the SW for MI in accordance with the requirements of documents of international and regional organizations of legislative metrology OIML and WELMEC were defined. A universal MI SW testing algorithm was proposed. It was proposed to apply approaches based on the requirements of documents and guidelines of international and regional metrology organizations for the preparation of special universal checklists for testing the software of virtually all categories of measuring equipment at the national level. This will confirm the authenticity and quality of the MI SW appraisals.